Monocytosis in polycythemia vera: Clinical and molecular correlates. Issue 7 (26th May 2017) - Barraco, Daniela; Cerquozzi, Sonia; Gangat, Naseema; Patnaik, Mrinal M.; Lasho, Terra; Finke, Christy; Hanson, Curtis A.; Ketterling, Rhett P.; Pardanani, Animesh; Tefferi, Ayalew
Abstract: Monocytosis (absolute monocyte count, AMC ≥ 1 × 10 9 /L) might accompany a spectrum of myeloid neoplasms, other than chronic myelomonocytic leukemia (CMML). In the current study, we examined the prevalence, laboratory and molecular correlates, and prognostic relevance of monocytosis in polycythemia vera (PV). Among 267 consecutive patients with World Health Organization (WHO)‐defined PV, 55 (21%) patients displayed an AMC of ≥1 × 10 9 /L and 18 (7%) an AMC of ≥1.5 × 10 9 /L. In general, PV patients with monocytosis were significantly older and displayed higher frequencies of leukocytosis (81% vs. 50% at AMC ≥1 × 10 9 /L) and TET2 / SRSF2 mutations (57%/29% vs. 19%/1% at AMC ≥ 1.5 × 10 9 /L). In univariate analysis, AMC ≥1.5 × 10 9 /L adversely affected overall (OS; P  = .004; HR 2.6, 95% CI 1.4‐4.8) and myelofibrosis‐free (MFFS; P  = .02; HR 4.4, 95% CI 1.3‐15.1) survival; during multivariable analysis, significance was borderline sustained for OS ( P  = .05) and MFFS ( P  = .06). Other independent risk factors for OS included unfavorable karyotype ( P  = .02, HR 3.39, 95% CI 1.17‐9.79), older age ( P  < .0001, HR 3.34 95% CI 1.97‐5.65), and leukocytosis ≥15 × 10 9 /L ( P  = .004, HR 2.04, 95% CI 1.26‐3.29). In conclusion, in the current study, we encountered a higher than expected prevalence of monocytosis in patients with PV and the mutation profile and age distribution of PV patients with monocytosis is akin to those of patients with CMML and might partly contribute to their worse prognosis.